Difluoromethylornithine: The Proof is in the Polyamines - Jeter, Joanne M. (2012)
In this issue, Kreul and colleagues report a retrospective review of long-term efficacy and toxicity for subjects participating in a Phase III study of difluoromethylornithine (DFMO) for prevention of nonmelanoma skin cancer (NMSC)(1). They conclude that those treated with DFMO had a nonsignificant, persistent decrease in NMSC after completion of treatment and that treatment with DFMO did not result in late toxicity after the discontinuation of treatment. We review the data on DFMO as a chemopreventive agent for skin and other cancers, discuss the necessary qualities of a cancer chemopreventive agent, and reflect on the requirements for a well-conducted cancer chemoprevention study, including the rationale for long-term follow-up in cancer prevention studies.